Puma: how sustainability accounting creates a win-win for companies and stakeholders - Huchzermeier, Arnd (Henry Stewart Talks, 2019)
This case study examines Puma’s decision to create an Environmental Profit and Loss account to increase the sustainability of their business. They measured the activities that harmed nature (loss) and those that benefited nature (profit). In this way corporate decisions are founded on impacts on the environment as well as on impacts on profitability.